Development of Non-Text Book on Flora and Fauna Diversity in the Mangrove Ecotourism Area, Karang Gading Wildlife Reserve, North Sumatra - Rensiva Ray Pehulisa; Mufti Sudibyo; Melva Silitonga (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2024)
This type of research is R & D (Research and Development) which aims to produce a certain product that requires previous trials (Semiawan, 2007) with a 4-D model that has been developed by Thiagarajan. This research developed a Non-Text Book on Flora and Fauna Diversity in Ecotourism Areas, Kab. Langkat Timur, North Sumatra, and researched the Mangrove Ecotourism Development Area, Karang Gading Wildlife Reserve, North Sumatra, using literature.This research was carried out with the aim of: (1) The feasibility of the contents of the non-text book Flora and Fauna Diversity in the North Sumatra Mangrove Ecotourism Development Area according to material expert validation received very feasible criteria with an average percentage of 83.33%; (2) The feasibility of the contents of the book Diversity of Flora and Fauna in the Karang Gading Mangrove Ecotourism Development Area, North Sumatra, according to design expert validation, received very appropriate criteria with an average percentage of 82.70%; (3) The appropriateness of the contents of the non-text book, Flora and Fauna Diversity in the Karang Gading Mangrove Ecotourism Development Area, North Sumatra, according to the validation of language experts, received very appropriate criteria with an average percentage of 83.33%; (4) The utilization of the book "Diversity of Flora and Fauna in the Karang Gading Mangrove Ecotourism Development Area, North Sumatra" in the ecotourism development of the same area can be considered moderately effective, as shown by an N-Gain value of 0.5.